Calibration of the LDI/CDTN Whole Body Counter us-ing two physical phantoms - Fernanda Guerra Paiva; Bruno Melo Mendes; Marco Aurélio Lacerda; Jaqueline Rosária Pinto; Sônia Prates; Nelson Nascimento Filho; Bernardo Maranhão Dantas; Ana Letícia Dantas; Telma Cristina Ferreira Fonseca; Teógenes Augusto da Silva (Brazilian Journal of Radiation Sciences, 2017)
The Laboratory of Internal Dosimetry of the Center for Development of Nuclear Technology (LDI/CDTN) is responsible for routine monitoring of internal contamination of the Individuals Occupationally Exposed (IOEs) at the Unit for Research and Production of Radiopharmaceuticals (UPPR/CDTN), the Research Reactor TRIGA-IPR-R1/CDTN and other workplaces of the institute where there is a risk of accidental intakes. Additionally, LDI supports the Institute of Radiation Protection and Dosimetry (IRD/CNEN) to attend radiological emergencies. The determination of photon emitting radionuclides in the human body requires the use of calibration techniques in different counting geometries for converting the count rates into activity in organs and tissues. This paper presents and discusses the calibration of the LDI/CDTN Whole Body Counter (WBC) using a standard BOMAB phantom (Bottle Mannequin Absorber) compared to a home-made phantom produced with Polyethylene Terephthalate bottles (PET). Initially, the BOMAB was filled with a cocktail containing 60Co, 137Cs and 133Ba. The phantom was counted at the LDI whole body counter and an Efficiency x Energy curve was obtained. Subsequently the PET-BOMAB was filled with the same standard source and a second curve was determined. The efficiency values in each region of interest as well as the shape of both curves were found to be equivalent. The results validate the use of the PET-BOMAB for the calibration of whole body geometry applied to the measurement of high energy radionuclides in the energy region evaluated in this work.